Evaluation of Policy in Tourism Development at Manohara Beach, Meureudu Sub-District, Pidie Jaya Regency - cut sah kha mei zsazsa; Boby Indra Prayoga (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This research is taken from the background of the problem at the beginning that visitors to Manohara Beach are not as crowded as before. Development of Manohara Beach tourism needs to be considered in order to attract more tourists. The positive impact of the increasing number of tourists visiting is the increasing economy of the surrounding community and increasing income for the Regional Government. However, evaluating tourism development requires several important things to be considered, so that the evaluation can run effectively & efficiently. The purpose of this study was to find out how to evaluate policies in tourism development at Manohara Beach, Meureudu District, Pidie Jaya Regency. The research method used is descriptive qualitative using interviews and documentation as data collection, with 5 informants. This study focuses on evaluating the development of Manohara Beach tourism using tourism development components that are used as indicators in measurement. The conclusion is that for tourism development based on components, namely physical aspects, attractiveness aspects, accessibility aspects, facilities aspects and social, economic, and cultural aspects, it is still not good. Keywords: Evaluation, Policy, Tourism Development